Analisis Kesesuaian Soal Ulangan Akhir Semester Ips Terpadu Dengan Implementasi Kurikulum 2013 Di SMP Negeri 1 Sambi Boyolali - HARLINA, SITI HIDAYATI; , Drs. Budi Sutrisno M.Pd (2015)
The purpose of this study to determine the level of validity and reliability of items and megetahui how well the level of difficulty as well as distinguishing items UAS Integrated Social VII grade students of SMP Negeri 1 Sambi, Boyolali 2014/2015 school year, as well as to determine the suitability of the application of the evaluation with the evaluation criteria according to the curriculum in 2013. This research is a quantitative explanatory. Population subjects in this study are all the items along with answer keys and answer sheets of the students. While the object is the entire population of students of class VII SMP Negeri 1 Sambi, Boyolali. The technique using proportional random sampling sampling.Teknik data collection using interviews and documentation. Normality Test Test is a prerequisite. Analysis using the formula of validity, reliability, level of difficulty matter, distinguishing and Test One Sample T-test with a significance level of 5%. Content validity of the results of data analysis in the final replay item odd semester for social studies class Integrated VII SMP Negeri 1 Sambi, Boyolali whole matter (100%) in accordance with the material in the curriculum syllabus 2013. While the validity of the construction there were 68% who had a valid item and 32% of items are invalid. That the value of Alpha Cronbach 'value r = 0.839> r table = 0.195 it can be stated Reliable. The level of difficulty in the classification difficult is 10% and is as much as 60% and 30% easy (with a note about the numbers, there are 2 or 4% there are questions that have provided the correct answers all). There is a 34% distinguishing items that are classified ugly (note there are two numbers matter or 4% are questions that have provided the correct answers all), 26% adequate, 32% good and 8% excellent. Test one sample t-test was 0.269 <t_tabel 2,045 or 0.269> of the value of probability (Sig) is 0.05 so that Ho accepted. Keywords: Suitability Analysis Problem, Level difficulty, Power differentiator